Theoretical estimation of the annual generation of biogas by the sanitary land of consortium CIAS - Hellen Luisa de Castro e Silva (Revista DAE, 2020)
With the advent of the National Solid Waste Policy, waste management plan has been viewed as strategy for competitiveness in climate change. In this sense, the search for technologies that reduce emissions based on the use of gases combined with the processes of recycling, reuse and minimization in the generation of wastes, has been corroborated for investments in research and expansion of alternative sources of energy. As a result, with the increasing production of waste due to the high rate of population growth combined with consumption, it is necessary to prepare a waste management plan with sustainable development for municipalities. In view of this fact, the purpose of this study was to analyze the economic viability of the biogas energy use generated by the São Paulo State Intermunicipal Consortium (CIAS), formed by the municipalities: Cajamar, Campo Limpo Paulista, Jundiaí, Louveira, Várzea Paulista and Vinhedo in projections of 20 years for different populations. For the production of gas projection, this study used the software LandGEM® developed by United States Environmental Protection Agency (US EPA). In this study, the utilization power equations are shown, as well as the energy produced from the estimated total population, which can be used for preliminary studies in other consortia.